Gender Equality Principle: Application in ECtHR’s Practice - Karvatska, Svitlana; Toronchuk, Ivan; Manyk, Alyona (LUMEN Media Ltd.,LUMEN, 2021)
The article is devoted to analyzing the decisions of the European Court of Human Rights (ECtHR), which concerned the issue of gender equality, distinctive features of the application of a gender equality principle by the ECtHR. Based on a study of ECtHR's rulings, it is noted that the concept of gender equality as one of the objectives of the Council of Europe has been applied by the ECtHR since the early 1990s. The ECtHR's approaches to dealing with gender equality cases are characterized both through the prism of non-discrimination (applying Article 14 of the European Convention on Human Rights in combination with other articles) and through complaints about violations of rights guaranteed by other ECHR articles. The analysis shows that, on the one hand, ECtHR emphasizes that gender equality is considered as one of the critical principles of the ECHR. However, on the other hand, significant difficulty in gender discrimination cases is the Court's possibility to refuse to analyze the case in the context of Article 14th content of the Convention. The possibility of giving the Court to states a vast margin of appreciation in determining domestic policies on gender equality is ambiguously manifested in judicial practice. The conclusion states that the need to ensure gender equality can be considered by the ECtHR as a legitimate aim and can serve as an appropriatebasis for interfering with the exercise of certain rights and freedoms enshrined in the Convention.
Keywords: gender equalit; ECtHR case law; discrimination; domestic violence; gender stereotypes